Exploring the Implementation of Wordwall in English Learning for PKPBI Students in UIN Malang - Nasru Ilahiyati; Syariful Muttaqin; Zuliati Rohmah (Universitas Teuku Umar, 2025)
This study investigates the implementation of Wordwall as a multimodal digital learning tool to enhance English vocabulary acquisition among third-semester PKPBI students from Tadris Mathematics and Qur’anic Interpretation majors at UIN Malang. Employing a descriptive qualitative design, data were collected through classroom observations, student interviews, documentation of student tasks, and pre- and post-tests. The findings reveal that Wordwall significantly improved students' vocabulary mastery, as demonstrated by the notable increase in post-test scores across both classes. Three main strategies, Meaning-Matching Strategy (MMS), Contextual Understanding (CU), and Pronunciation and Spelling Accuracy (PSA), were effectively applied through various Wordwall features such as Matching Game, Type the Answer, Wordsearch, and Open the Box. Students reported positive perceptions regarding Wordwall’s effectiveness, motivational appeal, engagement, learning experience, and visual design. The game-based format created an enjoyable and interactive learning environment that supported retention and contextual vocabulary use. However, a few students expressed challenges related to visual complexity and internet dependency, reflecting the need to align digital tools with students’ cognitive load and accessibility. This research contributes uniquely by integrating real-time classroom observations with student reflections from two distinct academic backgrounds and emphasizing Wordwall's role in personalized, multimodal vocabulary learning. The study highlights that while Wordwall is effective, its design and implementation must be adaptable to diverse learner profiles and technological readiness.Keywordsvocabulary acquisition, multimodal learning, Wordwall, student perception, digital learning tools.